Towards a Fundamental Astrometric Reference System behind the Magellanic Clouds: Spectroscopic Confirmation of New Quasar Candidates Selected in the Near-infrared - Ivanov, Valentin D. (2016)
Quasi-stellar objects (quasars) locatedbehind nearby galaxies provide anexcellent absolute reference system forastrometric studies, but they are diffi-cult to identify because of fore- andbackground contamination. We haveembarked on a programme to expandthe quasar reference system behindthe Large and Small Magellanic Clouds,the Magellanic Bridge and MagellanicStream. Hundreds of quasar candidateswere selected, based on their near-infrared colours and variability proper-ties from the ESO VISTA MagellanicClouds (VMC) Public Survey. A subsetof 49 objects was followed up with opti-cal spectroscopy with FORS2. We con-firmed the quasar nature of 37 objects(34 new identifications) that span a red-shift range from z ~ 0.5 to 4.1.